PENGARUH MORAL KARYAWAN DAN KOMITMEN ORGANISASIONAL TERHADAP ORGANIZATIONAL CITIZENSHIP BEHAVIOR PADA KOPERASI SIMPAN PINJAM CREDIT UNION SERVIAM KUPANG - Marsya Omega Nailius; Elly Lay; Leony M Ndoen (Universitas Nusa Cendana, 2021)
This research was conducted at KSP CU Serviam Kupang with the object of research are the KSP CU Serviam Kupang employees. This research is an associative research which provides an explanation of the causal relationship between variables based on two types of data, namely primary data and secondary data. Data collection was carried out using questionnaires, interviews and observation techniques. The sample in this study amounted to 67 people. The purpose of this study are (1) To analyze and describe Employee Morale, Organizational Commitment and Organizational Citizenship Behavior of KSP CU Serviam employees, (2) To analyze and describe the influence of Employees Morale on Organizational Citizenship Behavior of KSP CU Serviam employees, (3) To analyze and describe describe the effect of Organizational Commitment on Organizational Citizenship Behavior of KSP CU Serviam employees, (4) To analyze and describe the influence of Employees Morale and Organizational Commitment to Organizational Citizenship Behavior of KSP CU Serviam employees. Data analysis used descriptive statistical analysis techniques, inferential statistical analysis, multiple linear regression analysis, t test and F test. The results showed that (1) Employees Morale partially had a positive and significant effect on Organizational Citizenship Behavior in KSP CU Serviam Kupang, (2) Organizational Commitment partially had a positive and significant effect on Organizational Citizenship Behavior of KSP CU Serviam Kupang, (3) Employees Morale and Organizational Commitment simultaneously have a positive and significant effect on Organizational Citizenship Behavior of the KSP CU Serviam Kupang. Thus the company must continue to improve and pay attention to Employee Morale and Organizational Commitment in the company so that employees are always eager to work for the achievement of company goals. Keywords : Employee Morale, Organizational Commitment, Organizational Citizenship Behavior.